The antibacterial, antibiofilm, antifogging and mosquitocidal activities of titanium dioxide (TiO2) nanoparticles green-synthesized using multiple plants extracts. Issue 6 (December 2020) - Achudhan, David; Vijayakumar, Sekar; Malaikozhundan, Balasubramanian; Divya, Mani; Jothirajan, Maragatha; Subbian, Karuppuchamy; González-Sánchez, Zaira Isabel; Mahboob, Shahid; Al-Ghanim, Khalid A.; Vaseeharan, Baskaralingam
Graphical abstract: Highlights: Azadirachta indica twigs, Ficus benghalensis and Syzygium aromaticum bud wrapped TiO2 NPs were synthesized and characterized. G- TiO2 NPs showed antibacterial and antibiofilm activity against Streptococcus mutans and Citrobacter freundii . G- TiO2 NPs exhibited anti-fogging activity. G- TiO2 NPs have shown good mosquito larvicidal activity. Abstract: In the present study, TiO2 nanoparticles (NPs) were green-synthesized for first time using the extracts of Azadirachta indica twigs, Ficus benghalensis and Syzygium aromaticum . The green-synthesized G-TiO2 NPs were widely characterized by UV-Vis spectroscopy, XRD, FTIR, DRS-UV, HR-TEM, EDX and Zeta potential. The shapes of the G-TiO2 NPs are crystalline and tetragonal. The antibacterial and antibiofilm activities of G-TiO2 NPs were tested against bacteria ( Streptococcus mutans and Citrobacter freundii ) and fungi ( Candida albicans ). Both the bacterial and fungal biofilms were inhibited at 100 μg mL −1 . Furthermore, the mosquito larvicidal activity was evaluated against the Zika virus vector Aedes aegypti . The mortality of A. aegypti was 98% at 75 μg mL −1 of G-TiO2 NPs. The LC50 and LC90 values were 12.2 and 61.21 μg mL -1, respectively. Additionally, the photocatalytic activity of G-TiO2 NPs was determined by the degradation of organic dye (methylene blue) and the pharmaceutical drug (paracetamol). The photocatalytic degradation efficacy of G-TiO2 NPs was greater against paracetamol (88%) compared to the methylene blue (70%).